Istnienie obowiązku alimentacyjnego jako przesłanka powstania prawa do świadczeń z funduszu alimentacyjnego - Andrzejewski, Marek (Wydział Prawa i Administracji UAM, 1985)
Every acquisition of rights to prestations (benefit payments) from the Alimony Fund is always preceded with a realization of duty of alimony (art. 4 of the Alimony Fund Act of July 18, 1974). The notion of duty of alimony does not have a precise meaning. The author attempts at reconstructing a meaning of that notion. It is found in the conclusion that adll legal bonds conséquent upon familly law regulation, connecting the person entitled with the person obliged, are the grounds for appearance of duties of alimony. On the base of the adopted criterion all duties of providing the means of maintenance and possibly means of education established according to the regulation of art. 753 of Gode of Civil Procedure and Family and Guardianship Code have to be considered as duties of alimony. Next the author discusses the previous evolution and trends of developement of the studied piremise of acquisition of a right to benefits from the Alimony Fund. The 1982 and 1984 amendments of .the Act prove, in the author's opinion, that a formerly tight bond between the existence and scope of duties of alimony and the existence and scope of the right to the Alimony Fund benefits is presently diminishing. Now, the benefits have in a lesser extent a substitute character vs. the unenforced .alimony payments as compared with the initial period of the Fund's functioning. It results from taking over alimony burdens by the State and discharging the obliged from the liability. It is mostly the case of those obliged to alimony payments in a further precedence. The author criticizes the postulates to develop the Fund in that direction. Such a trend would undoubtedly end up in eroding the institution of duty of alimony.
Existence of the duty of alimony as a premise of acquiring the right to benefits from the Alimony Fund